(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Tuberculosis meningitis remains a difficult disease to diagnose and treatment with a mortality rate of about 30%, and often leaves serious neurological sequelae. The respone of treament in patients with tuberculosis meningitis after initiation of anti-tuberculosis therapy is unclear. Objective: To evaluate clinical and cerebrospinal fluid response in patients with tuberculous meningitis during the first month of treatment at National Lung Hospital. Materials and methods: Conducted an observational study to evaluate the response within 30 days of treatment in patients with tuberculosis meningitis. All patients (n = 43) were treated with anti-tuberculosis drugs (Streptomycin, Rifampicin, Isoniazid, Pyrazinamide, Ethambutol) in combination with corticosteroids. Patients were monitored for clinical symptoms, laboratory tests, and cerebrospinal fluid. Results: The clinical symptoms improved early after 15 days were fever (65.1% to 30.2%), vomiting, nausea (39.5% to 9.3%), consciousness disturbance (62.8% to 44.2%), meningeal signs (97.7% to 74.4%). The symptoms improved after 30 days were headache (90.3% to 55.8%) and round muscle disorder (48.8% to 11.6%). The mean cerebrospinal fluid leukocyte decreased after 30 days (496 ± 539 to 237 ± 273 cells/mm3), but mean cerebrospinal fluid protein and glucose concentrations did not change significantly after 30 days. Conclusion: Patients with tuberculosis meningitis should be closely monitored clinical symptoms during the first month to assess treatment response. Lumbar puncture repeat should be performed after 30 days of treatment to assess treatment response based on cerebrospinal fluid leukocyte counts instead of protein and glucose concentrations.